PENGUKURAN KUALITAS PERANGKAT LUNAK WEBSITE PENDATAAN EKSKUL SISWA MENGGUNAKAN FUNCTION POINT - Rizky Parlika; Rayhan Rizal Mahendra; Muhammad Rafli Aulia Rojani Lutfi; Rizqy Khoirul Waritsin; Humam Maulana Tsubasanofa Ramadhan (LPPM Universitas Putera Batam, 2023)
The development of software or software has started even since the creation of electronic computers. Software contains electronic data stored in computer devices. Measurement is the foundation of every engineering discipline and applies to software engineering as well. To evaluate the performance of a system or process, a mechanism is needed to observe and determine the level of efficiency. In software measurement there is an application to measure the value of the software. There are several methods of measuring software, one of which is the function point. Function point is one method that can measure software. This method produces the points needed to assess how much the price of a software is. The points are divided into two categories, namely Crude Function Point (CFP) and Relative Complexity Adjustment Factor RCAF. By using these points, a fixed price can be determined for a software.